1985
DOI: 10.1029/ja090ia06p05345
|View full text |Cite
|
Sign up to set email alerts
|

“Electron conic” signatures observed in the nightside auroral zone and over the polar cap

Abstract: A preliminary search of the Dynamics Explorer 1 high‐altitude plasma instrument data base has yielded examples of “electron conic” signatures. The three example passes show an association with regions of downward electron acceleration and upward ion beams, but this is not true of all the electron conic events. The electron conic signatures are clearly discernible on energy‐flux‐versus‐time color spectrograms as pairs of discrete vertical bands which are symmetric about a pitch angle of approximately 180°. One … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 12 publications
4
45
0
Order By: Relevance
“…5 the central density cavities do meet the threshold condition for AKR; that is, the plasma frequency is less than one fifth of the electr_)n cyclotron frequency. Warm electron distributions within the density depletion appear conic -like as observed recently by Menietti and Burch (1985). If the potential drop is small, dipolar magnetic field geometry causes cooler electron distributions to appear to be upward -travelling beams or counter -streaming beams above 3000 -4000 km, agreeing with observations of U n et al (1984) and Sharp at al.…”
Section: Smooth Solutions Species Densities Andpotentialsupporting
confidence: 81%
“…5 the central density cavities do meet the threshold condition for AKR; that is, the plasma frequency is less than one fifth of the electr_)n cyclotron frequency. Warm electron distributions within the density depletion appear conic -like as observed recently by Menietti and Burch (1985). If the potential drop is small, dipolar magnetic field geometry causes cooler electron distributions to appear to be upward -travelling beams or counter -streaming beams above 3000 -4000 km, agreeing with observations of U n et al (1984) and Sharp at al.…”
Section: Smooth Solutions Species Densities Andpotentialsupporting
confidence: 81%
“…Electron conic distributions may be classified into two distinct types: uni-directional and bi-directional. Menietti and Burch (1985) first identified uni-directional electron conic distributions appearing as enhancements in the electron flux at pitch angles slightly closer to 90°than the loss cone angle. Burch et al (1990) showed test particle calculations consistent with observations indicating that bi-directional electron conic distributions are observed on auroral field lines within regions of parallel electron acceleration.…”
Section: Introductionmentioning
confidence: 97%
“…Upward-going electrons, meanwhile, have an energy dependent loss cone, generally indicative of the presence of parallel electric fields below the spacecraft (Halekas et al, 2008c). Finally, upward-going electrons have enhanced perpendicular flux at low energies-this type of oblique enhancement or "conic", often observed in Earth's auroral regions, can indicate electron heating (Menietti and Burch, 1985). Note that the conic feature appears more clearly in the solar wind frame than in the Moon or dHT frames, so it results partially, but not completely, from reflection from a moving obstacle.…”
Section: Electron Distribution Functionsmentioning
confidence: 99%
“…Other conic formation mechanisms include parallel heating/acceleration by time-varying electric fields (André and Eliasson, 1992) or other stochastic mechanisms (Temerin and Cravens, 1990), and perpendicular wave heating (Menietti and Burch, 1985;Roth et al, 1989). Parallel heating alone probably cannot explain the observed conics, given the enhanced perpendicular flux (Temerin and Cravens, 1990).…”
Section: Conic Formationmentioning
confidence: 99%